Prevalence of oral submucous fibrosis among habitual gutkha and areca nut chewers in Moradabad district - Nitin Kumar Nigam; K. Aravinda; Manu Dhillon; Siddharth Gupta; Satheesha Reddy; M. Srinivas Raju (Elsevier, 2014)
Background: To determine the prevalence and severity of oral submucous fibrosis (OSMF) among habitual gutkha, areca nut and pan chewers of Moradabad, India. Method: A survey was conducted for a period of one year in east, west, north and south zones of Moradabad district, Uttar Pradesh. One thousand habitual chewers were selected as study participants, using a stratified random sampling technique, between the ages of 11-40 yrs, with a habit of chewing gutkha, areca nut, pan for over a year. A detailed history was recorded and meticulous clinical examination was conducted. Evaluation of taste sensation, hearing, interincisal distance, clinical staging was done in the OSMF patients found amongst habitual chewers. The obtained data was statistically analyzed using an SPSS 16.5 version soft ware. Results: The prevalence of OSMF was 6.3% (63/1000) and gutkha chewing was the most common abusive habit (42/63) amongst OSMF patients. Stage 1, Stage 2, Stage 3 OSMF was seen in 28, 19 and 16 patients respectively. Restricted mouth opening, altered taste perception and defective hearing was observed in 37/63 (58.7%), 24/63 (38.09%) and 14/63 (22.22%) respectively. Conclusion: Our study shows a prevalence of 6.3% OSMF among habitual chewers of Moradabad. Prevalence and severity were more in urban and rural patients respectively.